2017
DOI: 10.1038/jp.2016.254
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of twin pregnancies complicated by gestational diabetes: a meta-analysis of observational studies

Abstract: Identification and subsequent treatment of GDM in twin pregnancy demonstrates a similar risk of adverse perinatal outcomes compared with non-GDM twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 47 publications
8
45
0
Order By: Relevance
“…However, we did not find this association in our study. Similar to results from a meta-analysis on GDM in twin pregnancies, our study found no associations to birth weight, gestational age, large or small for gestational age neonates, respiratory distress, neonatal hypoglycemic or low Apgar score [39].…”
Section: Discussionsupporting
confidence: 87%
“…However, we did not find this association in our study. Similar to results from a meta-analysis on GDM in twin pregnancies, our study found no associations to birth weight, gestational age, large or small for gestational age neonates, respiratory distress, neonatal hypoglycemic or low Apgar score [39].…”
Section: Discussionsupporting
confidence: 87%
“…Key words: gestational diabetes, pregnancy outcome, singleton, twins T he incidence of gestational diabetes mellitus (GDM) is increasing worldwide because of the increasing prevalence of obesity in women of reproductive age and advanced maternal age. 1 The incidence of GDM may be even greater in twin gestations, a known independent risk factor for GDM. 2,3 GDM is associated with maternal and neonatal complications in singleton pregnancies.…”
mentioning
confidence: 99%
“…The results suggested that twin pregnancies with and without GDM were at a similar risk for adverse outcomes. 23 Optimal glycemic control in twin pregnancies with GDM is also currently unknown. Improved glycemic control through dietary and medication intervention in twin pregnancies with GDM may not improve outcomes such as preeclampsia, early gestational age at delivery, and low birthweight.…”
Section: Discussionmentioning
confidence: 99%